Asymmetric effect of financial development and remittance on economic growth in MINT economies: an application of panel NARDL - Jamiu Adetola Odugbesan (SpringerOpen, 2021)
Abstract The empirical analysis examines the asymmetric effect of financial development and remittance on economic growth in MINT nations (Mexico, Indonesia, Nigeria, and Turkey). The present study utilized panel data covering the period from 1980 to 2019. The research objectives are to address the questions: (a) Is there a long-run association between economic growth and the regressors? (b) Do financial development and remittance trigger MINT nations' economic growth? Moreover, the present study applied both linear panel ARDL and the novel panel nonlinear ARDL to capture the asymmetric impact of development and remittance on economic growth. The outcomes of the linear ARDL disclosed that both financial development and remittance triggers economic growth positively. Furthermore, the outcomes of the NARDL disclosed that both positive and negative shocks in financial development increase economic growth. In addition, a positive and negative shock in remittance increases economic growth in the long-run.